Poverty eradication, government role and sustainable livelihood in rural Malaysia: an empirical study of community perception in northern Peninsular Malaysia - Sharifah Rohayah Sheikh Dawood; Khoo, Suet Leng (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
While Malaysia is moving towards achieving a developed nation status rural poverty persists causing people and rurality to lag far behind and under-developed. Thus, one of the most important factors considered by the government is to proliferate multi-dimensional, poverty eradication programmes. This study explored the effectiveness of the poverty eradication programmes implemented by the government in rural areas in three states of northern Peninsular Malaysia. Primary data were gathered from questionnaire survey and in-depth interviews of 122 rural communities. The findings revealed that most of the programmes needed further improvement as some villagers still did not have adequate access to the programmes. Various strategies from the community up to the local authority levels were further needed to help achieve a sustainable community livelihood for the villagers. More opportunities should be given to the rural people in terms of access to the social media as this can help educate them more on the types of development programmes provided by the government and how they can apply for them. Finally, there was a need for a more holistic approach in addressing the issue of poverty in the country and how rural people can be rescued from further difficulties.